The Effects of Ellagic Acid on Growth and Biofilm Formation of Candida albicans - Sepideh Nejatbakhsh; Mohsen Ilkhanizadeh-Qomi; Mehdi Razzaghi-Abyaneh; Zahra Jahanshiri (Pasteur Institute of Iran, 2020)
Introduction: Biofilm formation is one of the specific features of Candida albicans that protects it from antifungal agents and the host immune system. Also, Biofilm formation by C. albicans on the mucosal surfaces and medical devices are responsible for causing Candida nosocomial infection. Here, we investigated the effects of ellagic acid on C. albicans growth and biofilm formation regarding the expression of two essential genes that are involved in adhesion and yeast-hypha transition. Methods: The yeasts were treated with serial two-fold concentrations of ellagic acid (3.125-100 µg/ml) for 48 h at 35°C. The weights of the cultured yeasts were measured as an indicator of the fungal growth, and the biofilm formation was assessed by a tetrazolium salt (XTT) reduction assay. The expressions of HWP1 and ALS3 genes were assayed by real-time PCR. Results: Ellagic acid inhibited C. albicans growth 0.68%-82.44%, dose-dependently. The biofilm formation also reduced 2.61%-68.318%. Also, The expressions of HWP1 and ALS3 genes were notably suppressed by ellagic acid at different concentrations. Conclusion: Our results showed that ellagic acid is a potential candidate to eliminate C. albicans-generated biofilm by suppressing the expression of the involved genes.